A comparison of the cost of outpatient care delivered by Aam Aadmi Mohalla Clinics compared to other public and private facilities in Delhi, India - Charu C. Garg; Roopali Goyanka (Health Policy Plan., 2023)
Aam Admi Mohalla Clinics (AAMCs) were introduced in Delhi in 2015 as neighbourhood clinics to strengthen the delivery of primary care. To inform the policies on government investments for outpatient care, this study estimated the cost of outpatient care per visit in Delhi for 2019-20 for AAMCs and compared it with urban primary health centres (UPHCs), public hospitals, private clinics and private hospitals. Facility costs for AAMCs and UPHCs were also estimated. Using the data from a national health survey, government annual budgets and reports, a modified top-down methodology was adopted to measure the true cost of public facilities, taking into account both government expenditure and out-of-pocket expenditure (OOPE). Inflation-adjusted OOPE was used to measure the cost of private facilities. The cost per visit at a private clinic at (sic)1146 (US$16) was more than 3-times higher than that at a UPHC ((sic)325/US$5) and 8-times higher than that at AAMCs ((sic)143/US$2.0). These costs were (sic)1099 (US$15) and (sic)1818 (US$25) at public and private hospitals respectively. The annual economic cost per facility of a UPHC at (sic) 9 280 000/$130 000 is similar to 4-times that at AAMC ((sic)2 474 000/$35 000). Unit costs are found to be lower at AAMCs. Utilization for outpatient care has shifted in favour of public primary care facilities. Higher investment in public primary care facilities with expanded services for prevention and promotion, upscaled infrastructure and a gate-keeping mechanism can strengthen the delivery of primary care and promote universal health care at a lower cost.
Keywords: Waste to Energy; Municipal solid waste; Air pollution control; Health hazards; Toxicological effect; Environmental impact assessment